Mesenteric Transit Time Using Contrast-Enhanced Ultrasound (CEUS) Does Not Correlate with Disease Activity in Crohn’s Disease - Goertz, R. S.; Heide, R.; Bernatik, T.; Waldner, M. J.; Mudter, J.; Neurath, M. F.; Strobel, D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: Evaluation of mesenteric transit time (MTT) – measured by contrast-enhanced ultrasound – as a marker for inflammatory activity in Crohn’s disease. Materials and Methods: The time of maximum enhancement of the contrast agent in the superior mesenteric artery and vein was determined visually and by software analysis. The MTT was calculated as the difference between these two time points. Findings were correlated with the Harvey-Bradshaw Index (HBI) using the Pearson correlation coefficient (r). In addition, a healthy control group was evaluated both in the fasting state and 1, 2, 3 and 4 hours postprandially. Results: In 20 healthy controls the mean visual MTT during fasting was 9.76 ± 2.83 sec and decreased to a minimum 1 hour after the meal (6.6 ± 2.27 sec). 45 patients with Crohn’s disease (9 males, 36 females, mean age 35 years) had a mean HBI of 5.9 ± 4.7 points. The mean software-based MTT of 9.76 ± 3.7 sec was significantly higher (p = 0.034) than the mean visual MTT of 8.22 ± 3.05 sec. The two figures correlated well (r = 0.72, p < 0.001). The HBI correlated neither with the visual (r = 0.14, p = 0.371) nor with the software-based (r = 0.16, p = 0.293) MTT. Conclusion: The MTT decreases in the first two hours after eating. The visually assessed and the software-based MTT correlate well, however MTT does not correlate with disease activity in patients with Crohn‘s disease.
Keywords: CEUS; mesenteric transit time; Crohn’s disease; activity; quantification